Alice in Wonderland syndrome associated with mycoplasma infection. Issue 10 (31st August 2016) - Omata, Taku; Fujii, Katsunori; Kuroki, Haruo; Shimojo, Naoki
Abstract: Alice in Wonderland syndrome (AIWS) is a rare condition in which patients report distorted size perception of objects and their own bodies. Although specific causes and pathology have not been elucidated, an association between AIWS and infection has been suggested. To our knowledge, mycoplasma‐induced AIWS has not been examined. A girl aged 7 years 11 months presented with fever (temperature, 40°C) and cough. Although the fever disappeared after approximately 10 days, she complained that her mother's face suddenly appeared smaller to her. Subsequently, she complained that objects intermittently appeared smaller than normal. Particle agglutination test indicated elevated serum antibodies against Mycoplasma pneumoniae . The patient was therefore diagnosed the patient with AIWS secondary to mycoplasma infection. Although mycoplasma infection is known to cause various central nervous system symptoms, this is the first report involving AIWS, suggesting that mycoplasma could affect visual function in children.